PENGARUH PENGGUNAAN POWERPOINT INTERAKTIF BERBANTUAN CANVA TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS V SDN TIRTAYASA 3 - umiroh; Diana Ayu Rostikawati; Sohri Ramadhan Alfikri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of conceptual understanding in elementary school students is crucial, as they are in a key stage of cognitive development. Unfortunately, many teachers still rely on lecture methods and assignments that are later discussed verbally. As a result, students tend to be passive—merely taking notes, memorizing, and completing tasks at home without truly understanding the material. This study aims to examine the impact of using interactive PowerPoint media combined with Canva on students' conceptual understanding of the human respiratory system. The study employed a quantitative method using a quasi-experimental design, involving two classes: the experimental class (using Canva-assisted PowerPoint) and the control class (conventional method), each consisting of 25 students. Data collection used multiple-choice tests for pretest and posttest, and a student perception questionnaire. Data were analyzed using normality, homogeneity, and hypothesis tests. The result showed a significance value of 0.012 (<0.05), indicating a significant difference in posttest results. This suggests that Canva-assisted PowerPoint improves students' conceptual understanding effectively.